2022
DOI: 10.1097/nr9.0000000000000006
|View full text |Cite
|
Sign up to set email alerts
|

Trends of fecal calprotectin levels and associations with early life experience in preterm infants

Abstract: Background: Preterm infants are at risk for severe infections due to their immature immune systems. Factors such as early life pain/stress experiences and feeding may influence immune activation and maturation of immune systems. However, the underlying mechanism remains unclear. Fecal calprotectin (FCP) is a noninvasive surrogate biomarker of mucosal inflammation in the gastrointestinal tract and has been used in detecting intestinal inflammation in specific pediatric gastrointestinal disorders. Objective: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
4
0
2
Order By: Relevance
“…Calprotectin was significantly increased in Group B after 4 h of lairage at the slaughterhouse. Although the relationship between stress and calprotectin has not been fully studied, some studies in patients with inflammatory bowel disease have associated the presence of higher levels of stress with increased fecal calprotectin [41], and also in a study involving preterm infants from neonatal intensive care units found a relationship between cumulative pain/stress during hospitalization and fecal calprotectin concentrations [42].…”
Section: Discussionmentioning
confidence: 99%
“…Calprotectin was significantly increased in Group B after 4 h of lairage at the slaughterhouse. Although the relationship between stress and calprotectin has not been fully studied, some studies in patients with inflammatory bowel disease have associated the presence of higher levels of stress with increased fecal calprotectin [41], and also in a study involving preterm infants from neonatal intensive care units found a relationship between cumulative pain/stress during hospitalization and fecal calprotectin concentrations [42].…”
Section: Discussionmentioning
confidence: 99%
“…This stress is due to new situations that face the pigs at the slaughterhouse, with various stressful stimuli such as strange sounds and mixing with unfamiliar pigs [ 17 ]. Previous reports have indicated that stress can increase faecal CALP in humans, suggesting that this increase could be related to the regulation of the immune system by stress [ 18 ], while other reports have associated these increases with the activation of inflammatory processes in the gut that occurs in stressful conditions [ 19 , 20 ]. The increases found in our study in the stress due to pre-slaughter lairage were lower than those found in sepsis, however further studies with other types of stress should be performed to evaluate if in some cases the increases could be high enough to mask a septic situation.…”
Section: Discussionmentioning
confidence: 99%
“…Диагностическая ценность кальпротектина у детей раннего возраста также вызывает растущий интерес. Повышенные концентрации кальпротектина в кале коррелируют с тяжестью воспалительных процессов при воспалительных заболеваниях кишечника [8,9], но могут встречаться и у здоровых новорожденных [10]. До настоящего времени существуют противоречивые данные о референсных значениях данного маркера у детей первого года жизни, не определена его роль у детей первого года с аллергической энтеропатией [11,12].…”
Section: Abstract: Food Allergy Non-invasive Monitoring Intestinal Ep...unclassified
“…В нашем исследовании фекальный кальпротектин у детей с аллергической энтеропатией превышал показатели контрольной группы более чем в 5 раз. Это согласуется с данными проведенных ранее исследований [7,8] и подтверждает, что фекальный кальпротектин может служить достоверным маркером, позволяющим судить о выраженности воспалительного повреждения слизистой оболочки кишечника, в том числе аллергического генеза. При анализе определяемых показателей у детей с аллергической энтеропатией в различных возрастных группах мы не обнаружили статистически значимых различий, что косвенно подтверждает активное участие данного маркера именно в воспалительных изменениях кишечника и не может быть объяснено функциональной незрелостью детей данной возрастной группы.…”
Section: результаты исследования и их обсуждениеunclassified